2019
DOI: 10.3390/cancers11121950
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Adverse Events in Metastatic Melanoma Patients Treated with Combination BRAF Plus MEK Inhibitors Versus BRAF Inhibitors: A Systematic Review

Abstract: We reviewed the literature to assess the efficacy and risk of constitutional, cardiac, gastrointestinal, and dermatological toxicities of combined BRAF plus MEK inhibitors versus BRAF inhibitors alone in patients with metastatic melanoma with BRAF mutations. Searches were conducted in PubMed, Cochrane Database of Systematic Reviews, Google scholar, ASCO, Scopus, and EMBASE for reports published from January 2010 through March 2019. Efficacy, including progression-free survival (PFS) and overall survival (OS) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 28 publications
0
19
0
1
Order By: Relevance
“…Paradoxical activation of the MAPK pathway by BRAF inhibitors can increase the risk of the other cutaneous malignancies developing [31]. Combination therapy with a BRAF inhibitor plus a MEK inhibitor is associated with reduced dermatological toxicity, although a slightly worse gastrointestinal adverse event profile, compared with monotherapy [70]. Combination therapy with BRAF inhibitors and some immunotherapeutic agents can also be associated with increased toxicity; in particular, the combination of vemurafenib and ipilimumab (an anti-CTLA4 monoclonal antibody) was associated with marked hepatotoxicity [21,48].…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxical activation of the MAPK pathway by BRAF inhibitors can increase the risk of the other cutaneous malignancies developing [31]. Combination therapy with a BRAF inhibitor plus a MEK inhibitor is associated with reduced dermatological toxicity, although a slightly worse gastrointestinal adverse event profile, compared with monotherapy [70]. Combination therapy with BRAF inhibitors and some immunotherapeutic agents can also be associated with increased toxicity; in particular, the combination of vemurafenib and ipilimumab (an anti-CTLA4 monoclonal antibody) was associated with marked hepatotoxicity [21,48].…”
Section: Discussionmentioning
confidence: 99%
“…Dual inhibition of the MAPK pathway with the addition of MEKi therapy to BRAFi therapy has been demonstrated in subsequent clinical studies aimed at further improving efficacy results and reducing the toxicities associated with reactivation of the MAPK pathway, including the incidence of secondary malignancies ( 31 ). A scheduled treatment with both BRAFi and MEKi showed a better efficacy overall compared to BRAFi monotherapy ( 32 ). Three BRAFi- MEKi combination treatments (dabrafenib-trametinib, vemurafenib-cobimetinib, and encorafenib-binimetinib) are currently considered the standard treatments for patients with advanced BRAF-mutant melanoma ( 33 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, subtypes of AEs differed between these three different BRAF/MEK inhibitor pairs [40], which might be caused by the different immunomodulatory effects in melanoma patients [41]. Indeed, a pre-clinical study in a xenografted mouse melanoma model suggested that dabrafenib, but not vemurafenib, enhances the therapeutic effects of anti-PD1 Abs [41].…”
Section: Adverse Events With Braf/mek Inhibitorsmentioning
confidence: 99%
“…To date, little is known about the mechanisms of AEs developing from melanoma patients treated with BRAF/MEK inhibitors [40,42,43]. Among them, recently, Amagai et al reported a case series with pyrexia developing from advanced melanoma treated with E + B therapy, and suggested that serum levels of soluble CD163 as well as IFN-γ induced chemokines [C-X-C motif chemokine (CXCL9, CXCL10, CXCL11)] were increased in the pyrexia group compared with the non-pyrexia group [42].…”
Section: Adverse Events With Braf/mek Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation